Association Between the Risk of Hyperuricemia and Changes in Branched-Chain Amino Acids Intake Over Twelve Years: A Latent Class Trajectory Analysis From the China Health and Nutrition Survey, 1997–2009 - Ren, Xiyun; Wu, Shasha; Xie, Wei; Liu, Ying; Yang, Shucai (Frontiers in Nutrition, 2022)
Objective The aim of this study is to identify dietary branched chain amino acids (BCAA) consumption trajectories in the Chinese adult population and to assess their association with the risk of hyperuricemia (HU). Methods：Cohort data from the China Health and Nutrition Survey 1997–2009 were used in this study. A total of 6,810 participants aged ≥18 years were included. Participants were designated into four subgroups based on the trajectories of dietary BCAA consumption. Cox proportional hazards models were performed to explore the associations between different trajectories and the risk of HU after adjustment for potential confounders. Mediation analysis was performed to explore the intermediary effect of differential blood indexes between the trajectories and the risk of HU. Results Four distinct trajectory groups dietary BCAA consumption were identified. Compared with low stable trajectory group, high to low trajectory group was significantly associated with decreased risk of HU (HR 1.35 (95% CI 1.03 to 1.79)) with adjustment for covariates. Total cholesterol (TC), hemoglobin A1c (HbA1c), fasting blood glucose (FBG) and triglyceride (TG) play partial regulation roles between trajectories and HU. Conclusion Gradually decreasing dietary BCAA intake increased the risk of HU, which is at least partially mediated by TC, HbA1c, FBG, and TG levels.